Zarządzanie ryzykiem we współczesnych przedsiębiorstwach: kontekst strategiczny - Sus-Januchowska, Aleksandra (Risk management in organizations: a strategic dimension, 2007)
The purpose of the article is to present an organization’s business risk, through a strategie dimension. In dynamie markets, taking this kind of risk is one of the most important ways to a successful strategy. The article bases on literaturę studies of the subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 76-85